COURT STATISTICS – A TOOL FOR MANAGEMENT AND STRATEGIC PLANNING - Marina Matić Bošković (Revija za kriminologiju i krivično pravo)
Court statistics developed over the time from bureaucratic data collection to monitoring and evaluation of court performances and judicial reforms. In the Europe, the Council of Europe CEPEJ contributed to the promotion of court statistics as a tool for management over judiciary and evaluation of judicial performances. Modern use of statistical reporting requires setting of performance indicators, which tracking will enable monitoring of court performance and inform decision making on further actions. Some of performance indicators are recommended by the CEPEJ and are widely accepted, like clearance rate and disposition time. However, court statistics could include information beyond court cases, like financial data per court and human resource data, which could inform interventions in the area of human resource management and financial resource management, i.e. equalization of workload among courts and judges, as well as calculation of cost per case. The use of information and communication technologies (ICT) in the courts and court statistics contributed significantly to improvement of administration of justice, through development of automatized case management systems, automatic export of relevant reports on court performance based on predefined indicators. However, few preconditions are required for successful deployment of the ICT in judiciary. Countries were putting efforts to strengthen court statistics and some good practices were developed over time. Slovenia dashboard for improvement of disposition time and Serbian court maps for tracking backlog reduction are good examples that could be used replicated in countries with similar challenges and goals.